RELATIONSHIP BETWEEN ABO AND Rh D BLOOD GROUP PHENOTYPES AND MALARIA AMONG A POPULATION OF UNDERGRADUATE STUDENTS IN KANO, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
ABO and Rh D antigens have been linked to pathogenesis of P. falciparum malaria with some phenotypes being protective while other susceptible. However, the evidence is inconsistent. The aim of this study was to determine the frequencies of ABO and Rh D phenotypes and their association with malaria among undergraduates of Bayero University, Kano, Nigeria. ABO and Rh D phenotypes were determined by monoclonal antisera (Plamatec Lab. Ltd., Bridport, UK) and malaria was assessed using rapid diagnostic test (RDT) kits RMOM-02571 (Access Bio, Inc., NJ, USA).One hundred and fifty participants, 76 males and 74 females, were recruited for the study.73.33% of the participants were aged 18 – 24 years. Prevalence of malaria was 26%. There was no statistically significant association between malaria infection and sex (X2 = 0.429, p = 0.512), marital status (X2 = 0.025, p = 0.874), age categories (X2 = 7.213, p = 0.125), and use of ITN (X2 = 0.140, p = 0.709). Blood group O phenotype was the dominant ABO group (78%) followed by A (14%), B (4.7%), and AB (3.3%). Rh D positive were92.7%.There was statistically significant association between malaria and Rh D phenotypes (X2 = 4.171, p = 0.041), however, ABO phenotypes were not statistically associated with malaria (X2 = 7.326, p = 0.062).Prevalence of malaria among the participants was moderate, O phenotype was the dominant group followed by A, B, and AB. Rh D phenotype was associated with malaria while ABO phenotypes were not.
Keywords: malaria, ABO, Rh D, undergraduates, Kano